2022
DOI: 10.46939/j.sci.arts-22.1-a11
|View full text |Cite
|
Sign up to set email alerts
|

Padovan Hybrid Quaternions and Some Properties

Abstract: We define Padovan hybrid quaternions by using Padovan hybrid numbers and Padovan quaternion. We give the basic operation properties of Padovan hybrid quaternion numbers. We give some properties and identities such as the Binet formula, sum formula, the matrix representation, characteristic equation, norm, characteristic and generating function for these quaternions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The fourth-dimensional recurrences of the Narayana sequence are called quaternions. Similar studies can be found in [13][14][15][16][17][18].…”
Section: New Recurrences Obtained By Three-dimensional Approach To Na...supporting
confidence: 86%
“…The fourth-dimensional recurrences of the Narayana sequence are called quaternions. Similar studies can be found in [13][14][15][16][17][18].…”
Section: New Recurrences Obtained By Three-dimensional Approach To Na...supporting
confidence: 86%
“…The Padovan sequence is named after Richard Padovan who attributed its discovery to Dutch architect Hans van der Laan in his 1994 essay Dom and later were studied by many researchers [9,10,11]. This is sequence A000931 on the On-Line Encyclopedia of Integer Sequences (OEIS) [8].…”
Section: Introductionmentioning
confidence: 99%